17-channels S-band multiwavelength Brillouin/Erbium Fiber Laser co-Pump with Raman source - Ahmad, Harith; Zulkifli, Mohd Zamani; Latif, A. A; Thambiratnam, K.; Harun, S. W. (Institute of Physics Publishing, 2009)
In this paper, we propose and demonstrate a stable Brillouin–Erbium Fibre Laser (BEFL) capable of generating up to 17 lasing wavelengths in the ShortWave length (Sband) region. The proposed setup uses a 7.7 km Dispersion Compensating Fibre (DCF) to act as a nonlinear gain medium and a 30 m long DepressedCladding Erbium Doped Fibre (DCEDF) as an optical amplifier for amplification in the Sband region. The proposed BEFL has an optimum tuning range of 1499 to 1502 nm and is capable of generating 17 lasing wavelengths with peak powers of between –20 to –15 dBm when injected with a Brillouin Pump (BP) of 5 dBm at 1499 nm and a Raman Pump (RP) of 300 mW at 1420 nm.